2020
DOI: 10.3390/ijerph17051606
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Different Remediation Strategies Applied in Petroleum-Contaminated Soils

Abstract: Due to the increasing pollution by petroleum hydrocarbons (PHs), it is an important task to develop eco-friendly and highly efficient methods for remediating petroleum-contaminated soils. In this study, bioremediation technology was applied to remediate PHs contaminated soils, and the bacterial community structure and physicochemical characteristics of the soil treated using different bioremediation regimens were analyzed. Compared with the control condition (S0), the PHs removal efficiency of biostimulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…This is due to the lower hydrophobicity of the short and medium-chain alkanes; thus, they are more easily degraded, as other authors confirmed [9]. The percentage of removed hydrocarbons was 63% on average for alkanes and 50% for aromatics in 138 days, which is in line with the values obtained in other studies [5,29].…”
Section: Discussionsupporting
confidence: 87%
“…This is due to the lower hydrophobicity of the short and medium-chain alkanes; thus, they are more easily degraded, as other authors confirmed [9]. The percentage of removed hydrocarbons was 63% on average for alkanes and 50% for aromatics in 138 days, which is in line with the values obtained in other studies [5,29].…”
Section: Discussionsupporting
confidence: 87%
“…It has been well documented those microbial activities and physicochemical properties of soil have a marked impact on the effectiveness of phytoremediation of PHs [13,14]. A vast variety of microbial communities such as fungi, algae and bacteria take part in the complete mineralization of PHs [15]. Bacteria use the carbon from PHs to carry out their reproductive and metabolic mechanisms [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria use the carbon from PHs to carry out their reproductive and metabolic mechanisms [16,17]. Several isolated microbes of genera Achromobacter, Bacteroides, Acinetobacter, Microbacterium, Actinobacteria, Pseudomonas, Arthrobacter, Cellulomonas and Azobacter are known to be effective for PHCs degradation [15,18,19]. They produce a variety of enzymes to regulate the degradation pathways through different oxidations reactions [15,18,20] and lead to mineralization of PHs to produce CO 2 and H 2 O [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…Biostimulation alone is mostly practiced in soil remediation [ 108 , 109 , 110 , 111 ]. Indigenous micro-organisms remain deprived of nutrients in this natural environment.…”
Section: Bioremediation Methodsmentioning
confidence: 99%